Effect of antihypertensive treatment in isolated systolic hypertension (ISH) – systematic review and meta-analysis of randomised controlled trials - Mattias Brunström; Bo Carlberg; Sverre E. Kjeldsen (Blood Pressure, 2023)
Background Isolated systolic hypertension (ISH) in middle-aged and elderly is associated with high cardiovascular risk, but no randomised controlled trial has assessed the effect of antihypertensive treatment in ISH using today’s definition, i.e. systolic blood pressure (SBP) ≥140 mmHg and diastolic blood pressure (DBP) <90 mmHg. Methods A systematic review and meta-analysis of randomised controlled trials was performed. Studies with ≥1000 patient-years of follow-up, comparing more intensive versus less intensive BP targets, or active drug versus placebo, were included if the mean baseline SBP was ≥140 mmHg and the mean baseline DBP was <90 mmHg. The primary outcome was major adverse cardiovascular events (MACE). Relative risks from each trial were pooled in random-effects meta-analyses, stratified by baseline and attained SBP level. Results Twenty-four trials, including 113,105 participants (mean age 67 years; mean blood pressure 149/83 mmHg) were included in the analysis. Overall, treatment reduced the risk of MACE by 9% (relative risk 0.91, 95% confidence interval 0.88–0.93). Treatment was more effective if baseline SBP was ≥160 mmHg (RR 0.77, 95% CIs 0.70–0.86) compared to 140–159 mmHg (RR 0.92, 95% CIs 0.89–0.95; p = 0.002 for interaction), but provided equal additional benefit across all attained SBP levels (RR 0.80, 95% CIs 0.70–0.92 for <130 mmHg, RR 0.92, 95% CIs 0.89–0.96 for 130–139 mmHg, and RR 0.87, 95% CIs 0.82–0.93 for ≥140 mmHg; p = 0.070 for interaction). Conclusions These findings support antihypertensive treatment of isolated systolic hypertension, regardless of baseline SBP, to target SBP <140 mmHg and even <130 mmHg if well tolerated.